Complexity of the Doppler motion field of an active region - Bumba, V.; Klvaňa, M.; Garcia, A. (Известия Крымской астрофизической обсерватории, 2007)
We have investigated numerous sets of photoelectric measurements of the line-of-sight velocity and magnetic field components in active region NOAA 7757 (July 1994) and its wide surroundings. The observations, made during 8 days with electronically enhanced sensitivity of velocity measurements, show the complexity of motions in and around the spot group. The NOAA 7757 Doppler motion field represents a specific disturbance of the semiregular motion patterns of the quiet photosphere. Close to the solar disk center, there exists a striking difference in the concentration and organization of the line-of-sight motion components away from (red-shifted) and toward (blue-shifted) the observer in and outside the active region. In contradiction to the quiet photosphere, in the area occupied by the region’s magnetic field body, the red-shifted Doppler velocity components are strongly concentrated and organized into a few cellular-like structures, while the blueshifted motion components are considerably diluted, mostly surrounding this area. Moreover, this difference, most outstanding very close to the solar disk center, is less distinct as one moves away from it. This is an evidence of the verticality of the observed velocity components. The Evershed flow fits in the negative motion components system, the stability and lifetime of which probably depends on the magnetic field age, intensity and organization. Close to the disk center, we also observed a distinct cellular-like feature, formed from the blue-shifted motion components, with a small area of the weak red-shifted motion components in its center, encircling the dying part of the region’s magnetic field. We also show the relationship of the distribution of the active region’s magnetic and velocity fields with the structural patterns of the K3 CaII chromosphere. These seemingly trivial relations can reveal the distribution of motions in an active region.